The Influence of Snakes and Ladders Game Media on Handwashing with Soap (HWWS) Behavior among Elementary School Students in Central Aceh District - Rahmahdani, Yuni; Saputra, Irwan; Nurjannah, Nurjannah; Usman, Said; T. Maulana (PT Inovasi Pratama Internasional, 2025)
Diarrhea remains a leading health issue among school-aged children in Indonesia. In central Aceh District, particularly in Bies Subdistrict, the incidence of diarrhea has increased, with one the primary contributing factors being poor handwashing with soap (HWWS) practices. Health education using engaging methods, such as the Snakes and Ladders game, may improve children’s behavior related to HWWS. This study aimed to determine the effect of the Snakes and Ladders educational game on HWWS behavior, including knowledge, attitude, and practice, among fourth- and fifth-grade students in the Central Aceh District. A quasi-experimental design with a nonequivalent control group was employed, involving 80 respondents divided into an intervention and a control group. The intervention group received HWWS education through the Snakes and Ladders game, while the control group received no special treatment. Data were collected using structured questionnaires and analyzed using the Mann-Whitney U Test and Wilcoxon Signed-Rank Test. Based on the results of the Mann Whitney test, it showed that there was no significant difference in knowledge between the intervention and control groups during the pretest (p = 0.649), but there was a significant difference in the posttest (p = 0.002). Attitudes showed differences both before (p = 0.000) and after the intervention (p = 0.000). Likewise, actions, there were significant differences in the pretest (p = 0.019) and posttest (p = 0.000). Meanwhile, the Wilcoxon test showed that there was a significant increase between the pretest and posttest in the intervention group, both in knowledge (p = 0.004), attitudes (p = 0.000), and actions (p = 0.000). The snakes and ladders educational game is effective in improving HWWS behavior among elementary school children. It is recommended as an enjoyable and innovative method for health education in school-bassed health programs.